PELATIHAN SINGKAT TENTANG PENGETAHUAN DAN KETERAMPILAN DALAM DETEKSI DINI PERKEMBANGAN ANAK BALITA - Husni, Husni (Politeknik Kesehatan Kemenkes Bengkulu, 2017)
The incidence of child development deviation in Indonesia reached 13% -18%.About 16% of children under five years got neurodevelopmental and brain disorders frommild to severe. This study aimed to determine the effect of brief training by using Pre-Screening Questionnaire Development (KPSP) to improve the knowledge and skills ofparents in detection of child development. This study was quasi experimental with preposttest only. The population in this study were the parents / guardians of children atkinder garten of Baitul Izzah and Al Hasanah Bengkulu City. Samples were parents whohave never participated in training and at least high school education. Number of samples56 (28 intervention and 28 control) taken with concecutive sampling techniques. Datacollection were using questionnaire for knowledge and checklist for skills. Statistical testindependent t-test at the α 5% (one tail). The results showed the average age was 33years, the average income was 2.3 million per month, more mothers working and havehigher education. There were the difference in knowledge after being given brief trainingof 27.5 (p value = 0.000) and the difference in ability between the intervention andcontrol groups (p value = 0.000). Effectiveness of brief training to increase the knowledgeof 35%. factor affecting the mother's knowledge was the age (p 0.001; OR: 2.12). Weconcluded that parents are expected to apply the child development detection according toability at home and it is needed training for other parents.